Penerapan Metode Fuzzy Mamdani Dalam Menentukan Kelayakan Operasional Bus - Andi Yulia Muniar (Celebes Engineering Journal, 2021)
Today we meet many companies that provide transportation services, one of which is a bus. Buses are widely used by the community as a means of transportation in traveling long distances even between islands. However, many traffic accidents involving buses occur due to errors in the vehicle factor. Damage to bus parts is not paid attention to, so there is a risk of traffic accidents. Therefore, a system is needed to determine the operational feasibility of the bus by applying the MAMDANI Fuzzy method. The MAMDANI Fuzzy method can define values between conventional states such as yes or no, true or false, black or white, feasible or not feasible and so on. So this method will be very helpful in solving the problem of determining the feasibility of bus operations.